2012
DOI: 10.2172/1049477
|View full text |Cite
|
Sign up to set email alerts
|

CO2-based mixtures as working fluids for geothermal turbines.

Abstract: Sandia National Laboratories is investigating advanced Brayton cycles using supercritical working fluids for application to a variety of heat sources, including geothermal, solar, fossil, and nuclear power. This work is centered on the supercritical CO 2 (S-CO 2 ) power conversion cycle, which has the potential for high efficiency in the temperature range of interest for these heat sources and is very compact-a feature likely to reduce capital costs. One promising approach is the use of CO 2 -based supercritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…In addition to the investigation of different S-CO 2 configurations, researchers also carried out the comparison between pure CO 2 and CO 2 mixtures. Wright et al [102] developed an S-CO 2 cycle for low-temperature geothermal heat sources and conducted a system performance comparison when either CO 2 -mixture (CO 2 /butane) or pure CO 2 as a working fluid. The findings indicated that, at a turbine inlet temperature of 160 • C and a dry heat rejection temperature of 46.7 • C, the efficiency of the CO 2 -mixture cycle was 18.1%, while the efficiency of the pure CO 2 cycle was 15%.…”
Section: S-co 2 Cycle For Geothermal Power Systemsmentioning
confidence: 99%
“…In addition to the investigation of different S-CO 2 configurations, researchers also carried out the comparison between pure CO 2 and CO 2 mixtures. Wright et al [102] developed an S-CO 2 cycle for low-temperature geothermal heat sources and conducted a system performance comparison when either CO 2 -mixture (CO 2 /butane) or pure CO 2 as a working fluid. The findings indicated that, at a turbine inlet temperature of 160 • C and a dry heat rejection temperature of 46.7 • C, the efficiency of the CO 2 -mixture cycle was 18.1%, while the efficiency of the pure CO 2 cycle was 15%.…”
Section: S-co 2 Cycle For Geothermal Power Systemsmentioning
confidence: 99%
“…So far, a few studies have been conducted to discuss the feasibility and performance of the supercritical CO 2 -based mixture power cycle. For example, Sandia National Laboratories performed experimental tests on the compatibility of CO 2 mixtures with the turbomachinery and the compressor operation in the supercritical region of mixtures [18]. Jeong et al [19,20] developed a supercritical cycle model, based on the mixture properties.…”
Section: Current Status Of Co 2 -Based Mixturesmentioning
confidence: 99%
“…[1][2][3][4][5] Furthermore, the density of CO 2 is relatively higher compared to the conventional working fluid, such as air or steam, as sCO 2 Brayton cycle operates at high pressure, which automatically results in exceedingly smaller sizes and higher rotational speed of rotating machinery, [6][7][8] including radial turbine, compressor, and generator. For the Brayton cycle with sCO 2 as working fluid, where the output power is below 1 MW, all rotating machines are incorporated into a sCO 2 turbinealternator-compressor (TAC) unit, [9][10][11] which can reduce the cost and enable modular construction technology. 12 In the generator of sCO 2 TAC unit, the shaft-type gap between rotor and stator is filled with the lowtemperature sCO 2 with axial flow, which is used to transfer the heat generated by the rotating rotor, to effectively achieve the purpose of cooling the generator, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the density of CO 2 is relatively higher compared to the conventional working fluid, such as air or steam, as sCO 2 Brayton cycle operates at high pressure, which automatically results in exceedingly smaller sizes and higher rotational speed of rotating machinery, 6–8 including radial turbine, compressor, and generator. For the Brayton cycle with sCO 2 as working fluid, where the output power is below 1 MW, all rotating machines are incorporated into a sCO 2 turbine‐alternator‐compressor (TAC) unit, 9–11 which can reduce the cost and enable modular construction technology 12 …”
Section: Introductionmentioning
confidence: 99%